Customizable service-oriented Petri net controllers - Mendes, João M. (2009)
In industrial automation, service-orientation is a relatively new and ascending concept and thus, concrete integrated methodologies are missing to accomplish the required development tasks. A suitable approach is to use the powerful set of features that Petri nets formalism provides for such dynamic systems. This paper presents a token game template that is part of the open methodology for the development of customized Petri nets controllers, targeting the engineering of service-oriented industrial automation. This template is based on a state machine specification for the life-cycle of transitions that leaves several options open for extending it with features depending on the application. The practical use and implementation should bring, among others, featured-full and integrated modeling, analysis and control capabilities, which is required by service-oriented ecosystems. This core structure was used and validated in the development of control applications for an industrial automation system.